Control of Microtubule Dynamics by Stu2p Is Essential for Spindle Orientation and Metaphase Chromosome Alignment in Yeast - Kosco, Karena A. (The American Society for Cell Biology, 2001)
Stu2p is a member of a conserved family of microtubule-binding proteins and an essential protein in yeast. Here, we report the first in vivo analysis of microtubule dynamics in cells lacking a member of this protein family. For these studies, we have used a conditional Stu2p depletion strain expressing α-tubulin fused to green fluorescent protein. Depletion of Stu2p leads to fewer and less dynamic cytoplasmic microtubules in both G1 and preanaphase cells. The reduction in cytoplasmic microtubule dynamics is due primarily to decreases in both the catastrophe and rescue frequencies and an increase in the fraction of time microtubules spend pausing. These changes have significant consequences for the cell because they impede the ability of cytoplasmic microtubules to orient the spindle. In addition, recovery of fluorescence after photobleaching indicates that kinetochore microtubules are no longer dynamic in the absence of Stu2p. This deficiency is correlated with a failure to properly align chromosomes at metaphase. Overall, we provide evidence that Stu2p promotes the dynamics of microtubule plus-ends in vivo and that these dynamics are critical for microtubule interactions with kinetochores and cortical sites in the cytoplasm.